The Effect Of Addition Of Clay Lands /(Coagulant Aids), On The Color Purification Of Peat Water With Coagulation-Flocculation Method With Al2SO4 - Irwinsyah, Irwinsyah; Daud, Syarfi; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water is a blackish brown surface water And contains colors and turbidity that require effective treatment And efficient to be suitable for use by the society. Various types of coagulant continue to be developed one of which is the coagulant of clay with the addition of alum. The purpose of adding coagulant is to destabilize the colloids so that contacs and clumping of particles that will form a deposited floc. This study aims to calculate the efficiency of color and turbidity in peat water and compare the color quality, and turbidity with the standard of clean water quality standard (Permenkes 907 year 2002). The fixed variable used in this study was stirring speed of 100 rpm at contact time of 1 minute and 20 rpm at contact time 15 minutes. The free variable used consisted of 1 grams alum coagulant mass: 0.2 grams of clay soil, 1 grams alum coagulant mass : 0.4 grams of clay soil, 1 grams alum coagulant mass : 0.6 grams of clay soil, 1 grams alum coagulant mass : 0.8 grams of clay soil, 1.0 grams alum coagulant mass : l grams of clay soil . Highest removal efficiency and turbidity 86.45%, 97%, 82.14% at 1 g mass with particle size + 200 mesh.Keywords: Clay Land, Color, Water Peat, Turbidity, Al2SO4